THE APPLICATION OF PROJECT BASED LEARNING TECHNIQUE TO IMPROVE THE STUDENTS’ SKILL IN WRITING ANNOUNCEMENT TEXT AT THE ELEMENTARY GRADE OF LKP LIBERTY ENGLISH COURSE TANJUNGBALAI - Azmita, Sharmila (Faculty of Tarbiyah nad Teacher Training, 2024)
This study was aimed to find students' skills in writing announcement text which can be improved by using the project based learning technique. This study uses a classroom action research. The subject of this research is elementary grade of LKP Liberty English Course Tanjungbalai which consists of 11 female and 9 male. The total is 20 students. Qualitative research has been taken by making observations and interviews. Meanwhile, qualitative research was taken using a test consisting of a pre test and a post test. From the observation, it can be concluded that teaching writing announcement text has increased by using project based learning techniques. In the pre-test, the students' mean score was 54.85. Whereas in the post test 1, the students' mean score was 76.8 and the post test 2 was 88.4. In other words, the students’ skill in writing announcement text was improved. And based on the observation sheet and documentation, it showed that the expression and excitement of the students were also improved.